Modelamiento e implementación de un esquema de co-simulación basado en python para protección de sistemas de potencia simulados en power factory (2021)
This project focuses on designing and implementing a virtualized relay modeled in Python to be installed in a Virtual Relay in the Loop scheme, in terms of the project. The work consists of designing a Web interface that allows configuring a virtualized relay in the DIgSILENT PowerFactory power system simulation software and performing simulations under electrical fault conditions; The relay performs protection algorithms based on the IEEE / ANSI standard C37.2 and implementations of manufacturers such as SEL and Siemens to execute trip orders given a protection coordination. The interface allows a user to configure the ANSI 50, 61, Directional Overcurrent, 79 and 87L functions; in addition, select projects stored by the user in the PowerFactory software, define fault events and select the measurement points that will be processed by the relay. This document describes the stages and methodologies implemented to prepare the project. Finally, a test is performed with the IEEE 13 node case, modeled by the software developers.